2020
DOI: 10.1038/s41409-020-0986-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of reduced-toxicity conditioning protocols using fludarabine, melphalan combined with thiotepa or carmustine in allogeneic hematopoietic cell transplantation

Abstract: The age of patients undergoing allogeneic hematopoietic cell transplantation (allo-HCT) has increased during the last decades, mainly due to improved reduced-intensity/toxicity conditioning protocols. A reduced-intensity conditioning based on fludarabin, carmustin/BCNU and melphalan (FBM) has been previously developed at our institution. Since we observed detrimental effects in individual patients with compromised lung function, efforts have been made in order to replace BCNU by thiotepa (FTM) to reduce toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…34,35 In the allo-HSCT setting at our institution, we first reduced the dose of BCNU and later replaced it with thiotepa in reduced-intensity conditioning to decrease or eliminate the risk of lung toxicity. 36 De-escalation of the melphalan dose while maintaining the antitumor activity is a good alternative, especially for older and fragile patients with multiple myeloma. 37 The most suitable protocols for specific patients with advanced age, comorbidities, and/or impaired lung and cardiac function are important research questions that should be addressed in the future in the context of controlled randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In the allo-HSCT setting at our institution, we first reduced the dose of BCNU and later replaced it with thiotepa in reduced-intensity conditioning to decrease or eliminate the risk of lung toxicity. 36 De-escalation of the melphalan dose while maintaining the antitumor activity is a good alternative, especially for older and fragile patients with multiple myeloma. 37 The most suitable protocols for specific patients with advanced age, comorbidities, and/or impaired lung and cardiac function are important research questions that should be addressed in the future in the context of controlled randomized clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our previous studies have shown that both conditioning protocols based on two alkylating agents (FBM or FTM) have adequate anti-leukemic activity and were suitable for older patients or those with co-morbidities including impaired lung function. Hence, both protocols were comparable regarding adjusted OS [14][15] .…”
Section: Introductionmentioning
confidence: 79%
“…In previous single-center-based studies, it was shown that FBM and FTM protocols are comparable after adjusting for variables in uencing mortality in multivariate analysis 15 . This was con rmed using EBMT registry-based data in a preliminary analysis of the present study and allowed us to include FBM-and FTM-treated patients in the same group.…”
Section: Methodsmentioning
confidence: 93%
“…Although more than 7500 children receive this treatment annually in the United States and Europe, the success of this therapy is limited by a broad range of post-HCT pulmonary injuries that develop in 10 to 40% of pediatric recipients in response to chemotherapeutic toxicity, infection, and impaired or dysregulated immunity (1)(2)(3). Comprehensive assessment of pulmonary health before HCT conditioning is critical to identify high-risk patients who may benefit from modified conditioning chemotherapy regimens, closer surveillance, and risk-stratified treatments aimed at mitigating the development of irreversible pulmonary toxicity (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%